Foam structure catalyst as well as preparation method and application thereof
By using foam structure catalyst, the problems of low selectivity and poor stability during the conversion of glucose to 1,3-propylene glycol were solved, and efficient glucose hydrogenolysis reaction and the production of 1,3-propylene glycol were achieved.
Patent Information
- Application Number
- CN202311348216.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art has low selectivity and poor stability during the conversion of glucose to 1,3-propylene glycol.
A foam structure catalyst is used, which consists of a foam structure, metal M2 grown on the foam structure, metal M2Ox, heteropolyate of metal M2, and optionally tungsten oxide WOz1 and molybdenum oxide MoOz2, and is prepared by hydrothermal synthesis and reduction treatment.
The selectivity of 1,3-propylene glycol is improved, and the stability of the catalyst is ensured through the close interaction between tungsten/molybdate and foam metal, the cost of subsequent unit operation of glucose hydrogenolysis is reduced, and the production efficiency of 1,3-propylene glycol is improved.
Smart Images

Figure CN119838607A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a foam structure catalyst and a preparation method and application thereof, in particular to an application in glucose hydrogenolysis reaction. Background Art
[0002] Ethanol has a wide range of uses in the chemical industry, medical and health care, food industry, agricultural production and other fields. Ethanol can be used to make acetic acid, beverages, flavors, dyes, fuels, etc. In medicine, 70%-75% ethanol by volume is often used as a disinfectant. Ethanol can be used alone as automobile fuel or mixed with gasoline as a mixed fuel. Adding 5%-20% fuel ethanol to gasoline to make ethanol gasoline can reduce the pollution of automobile exhaust to the air. In addition, ethanol can also be added to gasoline as an anti-knock agent to replace tetraethyl lead.
[0003] 1,3-propanediol (1,3-PDO for short) is an important chemical raw material, widely used in the synthesis of plasticizers, detergents, preservatives, emulsifiers, polyesters and polyurethanes, and can also be used as antifreeze, solvents, protective agents, etc. The most important application is the preparation of polytrimethylene terephthalate (PTT) polyester fibers. PTT is a polyester material with excellent performance. It has the high performance of polyethylene terephthalate (PET) and the easy processing of polybutylene terephthalate (PBT). It also has the good resilience and anti-pollution properties of nylon, and is easy to dye and wear-resistant. It has great potential in the fields of carpets, engineering plastics, clothing fabrics, etc. It has broad application prospects and is currently a hot spot in the development of synthetic fibers internationally. It is predicted by experts to be one of the most important new fiber varieties in the 21st century. However, due to the high cost of raw materials for 1,3-PDO, its development has been restricted. Therefore, since the 1990s, the research and development of low-cost 1,3-PDO synthesis technology has become one of the hot topics.
[0004] There are three main industrial production methods for 1,3-PDO, namely acrolein hydration, ethylene oxide (EO) hydroformylation and bio-fermentation. Among them, acrolein hydration has relatively low technical difficulty, but poor technical and economic performance. At present, the processes with development prospects are mainly EO hydroformylation and bio-fermentation. The EO hydroformylation method has low production costs and mature technology, but large equipment investment and high technical difficulty, especially the complex catalyst system, harsh and unstable manufacturing process, and highly toxic ligands; and both the hydroformylation reaction and the hydrogenation reaction require the concentration of reactants and products to be controlled at a very low level, which greatly reduces the efficiency of the reactor in the two-step reaction. The bio-fermentation method uses renewable resources, has a clean production environment, few by-products, less pollution, mild reaction conditions, and simple operation, but it still needs to make breakthroughs in strains and processes. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of low selectivity and poor stability of glucose conversion into target products in the prior art. The present invention provides a foam structure catalyst and a preparation method and application thereof. The foam structure catalyst provided by the present invention can be used for glucose hydrogenolysis reaction, improves the selectivity of 1,3-propylene glycol, and forms a close interaction between the heteropolyacid salt and the metal M1 in the foam structure, thereby ensuring the stability of the catalyst.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a foam structure catalyst, wherein the foam structure catalyst comprises a foam structure and a metal M2, a metal oxide M2O grown on the foam structure. x and a heteropolyacid salt of a metal M2 and optionally tungsten oxide WO z1 and optionally molybdenum oxide MoO z2, , z1=2-3, z2=2-3; wherein the heteropoly acid salt is selected from one or more of tungstate and molybdate, M2 is selected from one or more of Cu, Ni, Fe, Zn and Co, x=0.5-1.5; the foam structure contains metals M1 and M1O y , M1 is selected from one or more of foamed iron, foamed nickel and foamed cobalt, and y=1-1.5.
[0007] The second aspect of the present invention provides a method for preparing a foam structure catalyst, the preparation method comprising the following steps:
[0008] (1) pre-treating the foam structure material to obtain a foam structure precursor;
[0009] (2) mixing a solution of a soluble tungsten salt and a solution of a metal M2 salt, or mixing a solution of a soluble molybdenum salt and a solution of a metal M2 salt to obtain a suspension of a heteropolyacid salt;
[0010] (3) mixing the foam structure precursor obtained in step (1) with the suspension of heteropolyacid salt obtained in step (2), and then performing hydrothermal synthesis, and then performing a first drying and a first calcination to obtain a first catalyst precursor;
[0011] (4) The first catalyst precursor obtained in step (3) is subjected to reduction treatment to obtain a foam structure catalyst.
[0012] The third aspect of the present invention provides a foam structure catalyst prepared by the preparation method described in the second aspect.
[0013] The fourth aspect of the present invention provides use of the foam structure catalyst described in the first aspect or the third aspect in stabilizing the hydrogenolysis of glucose.
[0014] Preferably, the foam structure catalyst is used for continuous hydrogenolysis of glucose in a fixed bed reactor.
[0015] A fifth aspect of the present invention provides a method for stabilizing hydrogenolysis of glucose, the method comprising:
[0016] In the presence of the foam structure catalyst described in the first aspect or the third aspect, the glucose aqueous solution is subjected to hydrogenolysis reaction to obtain C1-C4 monohydric alcohol and / or C2-C4 dihydric alcohol.
[0017] In the glucose hydrogenolysis reaction of the present invention, under the action of the foam structure catalyst, glucose can be efficiently converted into C1-C4 monohydric alcohol and / or C2-C4 dihydric alcohol, and higher selectivity of ethanol and 1,3-propylene glycol can be achieved.
[0018] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:
[0019] The foam structure catalyst provided by the present invention is a tungsten / molybdate-foam metal structure coupling catalyst, which has an open macroporous structure, promotes the mass transfer efficiency of the catalyst surface, and the synergistic effect formed between tungsten / molybdate and foam metal improves the selectivity of 1,3-propylene glycol in the complex reaction network of glucose hydrogenolysis reaction, and realizes the conversion of glucose into 1,3-propylene glycol with higher value. At the same time, the catalyst can be used to convert glucose in a continuous fixed bed reactor, reducing the cost of subsequent unit operations of glucose hydrogenolysis and improving the production efficiency of 1,3-propylene glycol.
[0020] In the foam structure catalyst provided by the present invention, a close interaction is formed between the heteropolyacid salt and the metal M1 in the foam structure, thereby ensuring the stability of the catalyst. On the other hand, the chemical state of the active sites on the catalyst surface can be adjusted by adding different types of M2 and M1 metals, thereby achieving the regulation of the distribution of glucose hydrogenolysis products. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The SEM image and element distribution diagram of the CoWO4 / Fe Foam catalyst obtained in Example 1;
[0022] Figure 2 HR-TEM image of the CoWO4 / Fe Foam catalyst obtained in Example 1;
[0023] Figure 3 This is the pyridine infrared spectrum of the CoWO4 / Fe Foam catalyst obtained in Example 1;
[0024] Figure 4The XRD patterns of Fe Foam, CoWO4 / Fe Foam and Zr / CoWO4 / Fe Foam catalysts after the reaction. DETAILED DESCRIPTION
[0025] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0026] The first aspect of the present invention provides a foam structure catalyst, the foam structure catalyst comprising a foam structure and a metal M2, a metal oxide M2O grown on the foam structure. x and a heteropolyacid salt of a metal M2 and optionally tungsten oxide WO z1 and optionally molybdenum oxide MoO z2, , z1=2-3, z2=2-3; wherein the heteropoly acid salt is selected from one or more of tungstate and molybdate, M2 is selected from one or more of Cu, Ni, Fe, Zn and Co, x=0.5-1.5; the foam structure contains metals M1 and M1O y , M1 is selected from one or more of foamed iron, foamed nickel and foamed cobalt, and y=1-1.5.
[0027] In some embodiments of the present invention, within the range of 3-10 nm from the surface of the foam structure catalyst, the molar ratio of M1:M2 is 4-9; wherein M1 in M1 species 0 The content of M2 is 5-25%, and M2 in M2 species 0 The content of tungsten species is 0-15%. 5+ The content is 30-55%, Mo in molybdenum species 5+ The content is 25-45%.
[0028] Preferably, within the range of 3-10 nm from the surface of the foam structure catalyst, the molar content ratio of M1:M2 is 7-9; wherein, the molar content ratio of M1 in the M1 species is 0 The content is 15-20%, M2 in M2 species 0 The content is 8-12%, and W in tungsten species 5+ The content is 40-50%, Mo in molybdenum species 5+ The content is 30-40%. The above results were obtained through XPS characterization.
[0029] In some embodiments of the present invention, the foam structure catalyst further comprises a metal M3 and an optional M3O supported on the foam structure and the heteropolyacid salt. z , wherein M3 is selected from one or more of Ru, Rh, Pd, Pt, Zr and Zn, 0 <z≤0-2。
[0030] In some embodiments of the present invention, the surface of the foam structure catalyst is within the range of 3-10 nm in depth: M3 and M3O z The total molar content is: 0-5%, of which M3 0 The content is 0-50%; the above results are obtained by XPS characterization.
[0031] In the present invention, M3 and optional M3O z On the catalyst surface, it is evenly distributed in the foam structure and the surface of heteropolyacid salts.
[0032] When Zn was selected as M3 and the catalyst was prepared by the excess impregnation method, a 1,3-propylene glycol selectivity of 64% was achieved in the hydrogenolysis of glucose over the Zn / CoMoO4 / Co Foam catalyst.
[0033] When Zr was selected as M3 and the catalyst was prepared by the excess impregnation method, an ethanol selectivity of 48% was achieved in the hydrogenolysis of glucose over the Zr / CoWO4 / Fe Foam catalyst.
[0034] It can be seen from the above that the addition of metal M3 can regulate the acidic sites on the catalyst surface. When the Zn additive is added, the B acid content on the catalyst surface increases, thereby achieving a higher selectivity for 1,3-propylene glycol in the glucose hydrogenolysis reaction; and after the Zr additive is loaded into the catalyst, the L acid content on the catalyst surface increases, thereby improving the selectivity for ethanol in the glucose hydrogenolysis reaction.
[0035] In some embodiments of the present invention, the average pore size of the foam structure catalyst is 400-3000 μm.
[0036] In some embodiments of the present invention, the surface of the foam structure catalyst has metal hydrogenation active sites and acid active sites.
[0037] The foam structure catalyst provided by the present invention is a tungsten / molybdate-foam metal structure coupling catalyst, which has an open macroporous structure, promotes the mass transfer efficiency of the catalyst surface, and the synergistic effect formed between tungsten / molybdate and foam metal improves the selectivity of 1,3-propylene glycol in the complex reaction network of glucose hydrogenolysis reaction, and realizes the conversion of glucose into 1,3-propylene glycol with higher value. At the same time, the catalyst can be used to convert glucose in a continuous fixed bed reactor, reducing the cost of subsequent unit operations of glucose hydrogenolysis and improving the production efficiency of 1,3-propylene glycol.
[0038] The second aspect of the present invention provides a method for preparing a foam structure catalyst, the preparation method comprising the following steps:
[0039] (1) pre-treating the foam structure material to obtain a foam structure precursor;
[0040] (2) mixing a solution of a soluble tungsten salt and a solution of a metal M2 salt, or mixing a solution of a soluble molybdenum salt and a solution of a metal M2 salt to obtain a suspension of a heteropolyacid salt;
[0041] (3) mixing the foam structure precursor obtained in step (1) with the suspension of heteropolyacid salt obtained in step (2), and then performing hydrothermal synthesis, and then performing a first drying and a first calcination to obtain a first catalyst precursor;
[0042] (4) The first catalyst precursor obtained in step (3) is subjected to reduction treatment to obtain a foam structure catalyst.
[0043] In the present invention, the heteropolyacid salt obtained in step (2) contains catalytic active sites, which are grown on the foam structure through hydrothermal synthesis in step (3), and then subjected to a first drying and a first calcination to obtain a foam structure catalyst precursor. In the catalyst precursor, a close interaction is formed between the heteropolyacid salt and the metal M1 in the foam structure, thereby ensuring the stability of the catalyst. On the other hand, the chemical state of the active sites on the catalyst surface can be adjusted by adding different types of M2 and M1 metals, thereby achieving the regulation of the distribution of glucose hydrogenolysis products.
[0044] The catalyst prepared by the present invention is a tungsten / molybdate-foam metal structure coupling catalyst, which has an open macroporous structure, promotes the mass transfer efficiency of the catalyst surface, and the synergistic effect formed between tungsten / molybdate and foam metal improves the selectivity of 1,3-propylene glycol in the complex reaction network of glucose hydrogenolysis reaction, and realizes the conversion of glucose into 1,3-propylene glycol with higher value. At the same time, the catalyst can be used to convert glucose in a continuous fixed bed reactor, reducing the cost of subsequent unit operations of glucose hydrogenolysis and improving the production efficiency of 1,3-propylene glycol.
[0045] In some embodiments of the present invention, the foam structural material is selected from one or more of foamed iron, foamed nickel and foamed cobalt.
[0046] Preferably, the average pore size of the foam structural material is 400-3000 μm;
[0047] In some embodiments of the present invention, the soluble tungsten salt is selected from one or more of sodium tungstate, ammonium metatungstate and ammonium tungstate.
[0048] In some embodiments of the present invention, the soluble molybdenum salt is selected from sodium molybdate and / or ammonium molybdate.
[0049] In some embodiments of the present invention, the metal M2 salt is selected from one or more of cupric chloride, cupric nitrate, cupric acetate, nickel chloride, nickel nitrate, nickel acetate, ferrous chloride, ferrous nitrate, zinc chloride, zinc nitrate, zinc acetate, cobalt chloride, cobalt nitrate and cobalt acetate; preferably cupric chloride and / or cobalt chloride.
[0050] In some embodiments of the present invention, the molar ratio of the sum of the soluble tungsten salt and the soluble molybdenum salt to the metal M2 salt is 0.5-1.5:1.
[0051] In some embodiments of the present invention, the molar ratio of the foam structure precursor to the heteropolyacid salt is 4-9.
[0052] In some embodiments of the present invention, the pretreatment comprises: treating with dilute acid at a temperature of 20-35°C for 0.5-1h, washing and filtering, and vacuum drying at 55-65°C for 10-14h.
[0053] Preferably, the dilute acid is selected from dilute hydrochloric acid or dilute nitric acid.
[0054] More preferably, the molar concentration of the dilute acid is 0.1-1%.
[0055] In some embodiments of the present invention, the conditions of the hydrothermal synthesis include: a temperature of 110-150° C. and a time of 6-24 h.
[0056] In some embodiments of the present invention, the first drying is performed at a temperature of 60-120° C. for a time of 10-12 hours.
[0057] In some embodiments of the present invention, the temperature of the first calcination is 400-600° C. and the time is 3-8 hours.
[0058] In some embodiments of the present invention, the reduction treatment conditions include: in a reducing gas with a H2 volume concentration of 5% to 100%, heating to 200-500°C at a rate of 1-10°C / min (preferably 2-5°C / min), and keeping the temperature for 1-20h. Preferably, the gas velocity of the reducing gas is 20-120mL / min.
[0059] In the present invention, the reduction treatment can be performed when preparing the catalyst or before use. For example, for an activator metal that is easily oxidized, it is preferred to perform the reduction treatment before use; for an activator metal that is not easily oxidized, the reduction treatment can be performed when preparing the catalyst or before use. Those skilled in the art can perform the reduction treatment according to actual needs.
[0060] In some embodiments of the present invention, between step (3) and step (4), the method further comprises:
[0061] (3') impregnating the first catalyst precursor obtained in step (3) with a solution of a metal M3 salt by an excess impregnation method, placing the catalyst precursor under negative pressure, and then performing a second drying and a second calcination to obtain a second catalyst precursor;
[0062] (4) The second catalyst precursor obtained in step (3') is subjected to reduction treatment to obtain a foam structure catalyst.
[0063] In the present invention, the addition of the M3 additive can finely control the chemical states such as the acidic species and relative proportions on the catalyst surface to achieve higher selectivity for the target product.
[0064] In some embodiments of the present invention, the metal M3 salt is selected from one or more of ruthenium nitrate, ruthenium chloride, rhodium nitrate, palladium nitrate, diamine dinitrate diammine platinum, chloroplatinic acid, zirconium oxynitrate, zirconium nitrate and zinc nitrate; more preferably selected from one or more of ruthenium nitrate, rhodium nitrate, palladium nitrate, diamine dinitrate diammine platinum and zirconium nitrate.
[0065] In some embodiments of the present invention, the excess impregnation method comprises: dissolving M3 salt in deionized water, and the M3 loading amount is 0.1-0.5 wt.%.
[0066] In some embodiments of the present invention, the negative pressure standing conditions include: temperature of 20-30° C., pressure of -0.05 to -0.07 MPa, and time of 5-10 min.
[0067] In some embodiments of the present invention, the second drying is performed at a temperature of 80-120° C. for a time of 10-12 hours.
[0068] In some embodiments of the present invention, the second calcination is carried out at a temperature of 400-600° C. and for a time of 2-6 hours.
[0069] In some embodiments of the present invention, the loading amount of the M3 salt calculated as M3 is 0.1-0.5 wt %.
[0070] The third aspect of the present invention provides a foam structure catalyst prepared by the preparation method described in the second aspect.
[0071] In the present invention, the foam structure catalyst prepared by the preparation method described in the second aspect can be recorded as M3 / M2WO x / M1 Foam or M3 / M2MoO x / M1 Foam catalyst.
[0072] The fourth aspect of the present invention provides use of the foam structure catalyst described in the first aspect or the third aspect in stabilizing the hydrogenolysis of glucose.
[0073] The present invention couples tungsten / molybdate and foam metal material M1 by hydrothermal synthesis, and completes the construction of active sites on the catalyst surface by in-situ reduction: the surface of the foam metal material is subjected to M1O generated in the hydrothermal synthesis process. x The components undergo an in-situ reduction process to generate metal element M1 on the catalyst surface. 0 As a hydrogenation active site; at the same time, through the growth of tungsten / molybdate components on the foam metal M1, the synergistic effect of Lewis acid and Bronsted acid sites is constructed on the catalyst surface, which promotes the isomerization of glucose into fructose and increases the generation of C3 intermediates with fructose as an intermediate. In addition, under the coupling effect of the Bronsted acid sites constructed on the catalyst surface and the hydrogenation active sites, the conversion of C3 intermediates to 1,3-propylene glycol is promoted. In addition, the Lewis acid and the hydrogenation active sites in the catalyst synergistically promote the direct hydrogenolysis of glucose into ethanol. In addition, in the present invention, the M3 species is loaded on the catalyst by a loading method, the surface acidity of the catalyst is adjusted, and the product distribution of the glucose hydrogenolysis reaction is changed. Wherein, M3 is selected from Ru, Rh, Pd, Pt, Zr and Zn. In addition, the catalyst prepared by the present invention introduces a foam metal structure with open macropores, improves the mass transfer efficiency of the catalyst surface, and inhibits the conversion of glucose into humus on the catalyst surface, which leads to the deactivation of the catalyst.
[0074] A fifth aspect of the present invention provides a method for stabilizing hydrogenolysis of glucose, the method comprising:
[0075] In the presence of the foam structure catalyst described in the first aspect or the third aspect, the glucose aqueous solution is subjected to hydrogenolysis reaction to obtain C1-C4 monohydric alcohol and / or C2-C4 dihydric alcohol.
[0076] In the present invention, C1-C4 monohydric alcohols include but are not limited to: ethanol;
[0077] In the present invention, C2-C4 diols include but are not limited to: 1,3-propylene glycol;
[0078] Specifically, the hydrogenolysis reaction is carried out in a continuous fixed bed reactor, and the foam structure catalyst is fixed with quartz wool within the corresponding range of the constant temperature zone of the heating device of the continuous fixed bed reactor; glucose aqueous solution and H2 are introduced into the continuous fixed bed reactor to carry out the hydrogenolysis reaction.
[0079] In some embodiments of the present invention, the hydrogenolysis reaction temperature is 175-295° C. and the pressure is 3-5 MPa.
[0080] In some embodiments of the present invention, the reaction gas for the hydrogenolysis reaction is hydrogen, and the flow rate of hydrogen is 35-95 mL / (min·g cat -1 ).
[0081] In some embodiments of the present invention, the concentration of glucose in the glucose aqueous solution is 25-80 g / L, and the flow rate of the glucose aqueous solution is 0.05-2 mL / (min·g cat -1 ).
[0082] In some embodiments of the present invention, the hydrogenolysis reaction is carried out in a continuous fixed bed reactor, and the height of the catalyst bed is 0.5-3 cm.
[0083] In some embodiments of the present invention, the molar selectivity of 1,3-propylene glycol is 5-55%, and the molar selectivity of ethanol is 10-48%.
[0084] The present invention is described in detail below by way of examples, but the protection scope of the present invention is not limited to the following description. In the following examples and comparative examples, if no specific conditions are specified, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be obtained through commercial channels.
[0085] In the following examples and comparative examples,
[0086] Example 1
[0087] A method for preparing a foam structure catalyst specifically comprises the following steps:
[0088] (1) The foamed iron with an average pore size of 1500 μm was treated with acid by immersing it in 0.1% dilute hydrochloric acid at 25° C. for 0.5 h, washed with water and filtered, and then vacuum dried at 55° C. for 10 h;
[0089] (2) mixing a sodium tungstate aqueous solution and a cobalt acetate aqueous solution in a molar ratio of 1:1 to obtain a suspension containing catalyst active sites;
[0090] (3) mixing the foamed metal material obtained in step (1) with the suspension obtained in step (2), and performing hydrothermal synthesis at 150° C. and maintaining for 6 hours; then performing a first drying at 120° C. and maintaining for 12 hours; and performing a first calcination at 400° C. and maintaining for 3 hours, to obtain a CoWO4 / Fe Foam catalyst precursor;
[0091] (4) The catalyst precursor prepared in the above step is placed in a reactor for reduction. The reduction conditions are: in a 100% H2 atmosphere, the temperature is raised to 300°C at a rate of 2°C / min, and the reduction is carried out for 10 hours. During the reduction process, the gas velocity is maintained at 80 mL / min to obtain a CoWO4 / Fe Foam catalyst.
[0092] Figure 1 The scanning electron microscope image and element distribution diagram of the CoWO4 / Fe Foam catalyst obtained in this example are shown in FIG. Figure 1 It can be seen that Fe, Co and W elements can be detected on the surface of the foam structure, and the three are in close contact, indicating that CoWO4 / Fe Foam is formed.
[0093] Figure 2 HR-TEM image of the CoWO4 / Fe Foam catalyst obtained in this example. Figure 2 It can be seen that the HR-TEM image of the catalyst shows the phase structure of the CoWO4 / Fe Foam catalyst, in which the CoWO4 and Fe3O4 species on the catalyst are in close contact, which is beneficial to the Fe 3+ An efficient synergistic effect is constructed between the B acid active site and the CoWO4 L acid active site, thereby improving the selectivity of 1,3-propanediol in the glucose hydrogenolysis reaction.
[0094] The molar content ratio of Fe:Co in the CoWO4 / Fe Foam catalyst obtained in this example is 4 from the surface to the depth of 3-10nm, where Fe 0 The content is 5%, Co in Co species 0 The content is 0%, W in W species 5+ The content is 30%. The above results were obtained through XPS characterization.
[0095] The CoWO4 / Fe Foam catalyst obtained above was used to carry out glucose hydrogenolysis in a continuous fixed bed reactor. The catalyst bed height was 3 cm. The reaction gas for the hydrogenolysis reaction was hydrogen, and the flow rate of hydrogen was 70 mL / (min·g cat-1 ), temperature is 205℃, pressure is 5MPa; flow rate of glucose aqueous solution is 0.1mL / (min·g cat -1 ), the concentration of glucose in the glucose aqueous solution is 25 g / L. The distribution of glucose hydrogenolysis products is shown in Table 1.
[0096] Table 1 Evaluation results of the activity of CoWO4 / Fe Foam catalyst for glucose hydrogenolysis
[0097]
[0098] Others: including products such as sorbitol, hexylene glycol and n-propanol.
[0099] Figure 3 The pyridine infrared spectrum of the CoWO4 / Fe Foam catalyst obtained in this example is shown in FIG. Figure 3 Visible, located in 1642 / 1545cm -1 The peaks at 1605 / 1574 / 1444cm can be attributed to the peaks caused by the adsorption of pyridine molecules on the active sites of B acid. -1 The peak is attributed to the infrared vibration peak caused by the adsorption of pyridine molecules on the L acid site. It is calculated that B / L = 0.17 on this catalyst. Under the synergistic effect of B acid and L acid sites, the rapid hydrogenolysis of glucose into 1,3-propylene glycol is promoted.
[0100] Example 2
[0101] A method for preparing a foam structure catalyst specifically comprises the following steps:
[0102] (1) treating the foamed cobalt with an average pore size of 3000 μm by immersing it in 0.1% dilute nitric acid at 25° C. for 0.5 h, washing it with water and filtering it, and then drying it in vacuum at 65° C. for 14 h;
[0103] (2) mixing an aqueous sodium molybdate solution and an aqueous cupric chloride solution at a molar ratio of 0.5:1 to obtain a suspension containing catalyst active sites;
[0104] (3) mixing the foamed metal material obtained in step (1) with the suspension obtained in step (2), and performing hydrothermal synthesis at 110° C. for 24 h; then performing a first drying at 60° C. for 10 h; and performing a first calcination at 600° C. for 8 h to obtain a CuMoO4 / Co Foam catalyst precursor;
[0105] (4) By the excess impregnation method, diamine dinitrate diplatinum diamine was dissolved in deionized water, and the Pt species was loaded on the CuMoO4 / Co Foam catalyst precursor with a loading amount of 0.5wt.%, and then allowed to stand under negative pressure for 10 minutes at room temperature; then a second drying was performed at 120°C for 10 hours; and a second calcination was performed at 400°C for 2 hours to obtain a Pt / CuMoO4 / Co Foam catalyst precursor.
[0106] (5) The Pt / CuMoO4 / Co Foam catalyst precursor prepared in step (5) is placed in a reactor for reduction. The reduction conditions are: in a 100% H2 atmosphere, the temperature is increased to 300°C at a rate of 2°C / min, and the reduction is performed for 10 hours. During the reduction process, the gas velocity is maintained at 80 mL / min; and a Pt / CuMoO4 / Co Foam catalyst is obtained.
[0107] The molar content ratio of Co:Cu in the CuMoO4 / Co Foam catalyst obtained in this example is 9 from the surface to the depth of 3-10nm, wherein the Co species contains 0 The content is 25%, Cu in Cu species 0 The content is 15%, Mo in Mo species 5+ The content is 45%, and Pt in Pt species 0 The content is 50%. The above results were obtained through XPS characterization.
[0108] The Pt / CuMoO4 / Co Foam catalyst obtained above was used to carry out glucose hydrogenolysis in a continuous fixed bed reactor. The catalyst bed height was 2 cm. The reaction gas for the hydrogenolysis reaction was hydrogen, and the flow rate of hydrogen was 90 mL / (min·g cat -1 ), temperature is 175℃, pressure is 3MPa; flow rate of glucose aqueous solution is 0.2mL / (min·g cat -1 ), the concentration of glucose in the glucose aqueous solution is 80 g / L. The distribution of glucose hydrogenolysis products is shown in Table 2.
[0109] Table 2 Evaluation results of glucose hydrogenolysis activity of Pt / CuMoO4 / Co Foam catalyst
[0110]
[0111] Others: including products such as sorbitol, hexylene glycol and n-propanol.
[0112] Example 3
[0113] A method for preparing a foam structure catalyst specifically comprises the following steps:
[0114] (1) treating the nickel foam with an average pore size of 400 μm by immersing it in 0.5% dilute hydrochloric acid at 45° C. for 0.5 h, washing it with water and filtering it, and then drying it in vacuum at 60° C. for 12 h;
[0115] (2) mixing an aqueous ammonium molybdate solution and an aqueous ferrous chloride solution at a molar ratio of 1.5:1 to obtain a suspension containing catalyst active sites;
[0116] (3) mixing the foamed metal material obtained in step (1) with the suspension obtained in step (2), and performing hydrothermal synthesis at 120° C. for 12 hours; then performing a first drying at 100° C. for 12 hours; and performing a first calcination at 500° C. for 4 hours to obtain a FeMoO4 / Ni Foam catalyst precursor;
[0117] (4) by an excess impregnation method, ruthenium nitrate was dissolved in deionized water, and Ru species was loaded on the FeMoO4 / NiFoam catalyst precursor, with a loading amount of 0.1 wt.%, and the mixture was placed under negative pressure at room temperature for 10 min; then a second drying was performed at 120° C. for 10 h; and a second calcination was performed at 400° C. for 2 h to obtain a Ru / FeMoO4 / NiFoam catalyst precursor;
[0118] (5) The Ru / FeMoO4 / Ni Foam catalyst precursor prepared in the above step is placed in a reactor for reduction. The reduction conditions are: in a 100% H2 atmosphere, the temperature is increased to 300°C at a rate of 2°C / min, and the reduction is carried out for 10 hours. During the reduction process, the gas velocity is maintained at 80 mL / min to obtain a Ru / FeMoO4 / Ni Foam catalyst.
[0119] The Ru / FeMoO4 / Ni Foam catalyst obtained in this example has a Ni:Fe molar content ratio of 5 from the surface to the depth of 3-10 nm, wherein Ni 0 The content is 15%, Fe in Fe species 0 The content is 10%, Mo in Mo species 5+ The content is 35%, Ru in Ru species 0 The content is 0%. The above results were obtained through XPS characterization.
[0120] The Ru / FeMoO4 / Ni Foam catalyst obtained above was used to carry out glucose hydrogenolysis in a continuous fixed bed reactor. The catalyst bed height was 1 cm. The reaction gas for the hydrogenolysis reaction was hydrogen, and the flow rate of hydrogen was 35 mL / (min·g cat - 1), temperature was 245℃, pressure was 3 MPa; flow rate of glucose aqueous solution was 0.2 mL / (min·g cat - 1 ), the concentration of glucose in the glucose aqueous solution is 70 g / L. The distribution of glucose hydrogenolysis products is shown in Table 3.
[0121] Table 3 Evaluation results of the activity of Ru / FeMoO4 / Ni Foam catalyst for glucose hydrogenolysis
[0122]
[0123] Others: including products such as sorbitol, hexylene glycol and n-propanol.
[0124] Example 4
[0125] A method for preparing a foam structure catalyst specifically comprises the following steps:
[0126] (1) The foamed iron with an average pore size of 800 μm was treated with acid by immersing it in 0.5% dilute hydrochloric acid at 45°C for 0.5 h, then washed and filtered, and then vacuum dried at 60°C for 12 h;
[0127] (2) mixing an aqueous solution of ammonium metatungstate and an aqueous solution of copper nitrate in a molar ratio of 1:1 to obtain a suspension containing catalyst active sites;
[0128] (3) mixing the foamed metal material obtained in step (1) with the suspension obtained in step (2), and performing hydrothermal synthesis at 120° C. for 12 h; then performing a first drying at 100° C. for 12 h; and performing a first calcination at 550° C. for 6 h to obtain a CuWO4 / FeFoam catalyst precursor;
[0129] (4) Ruthenium chloride was dissolved in deionized water by an excess impregnation method, and Ru species was loaded on the CuWO4 / FeFoam catalyst precursor with a loading amount of 0.1 wt.%, and the mixture was placed under negative pressure at room temperature for 10 min; then a second drying was performed at 120°C for 10 h; and a second calcination was performed at 400°C for 2 h to obtain a Ru / CuWO4 / FeFoam catalyst precursor;
[0130] (5) The Ru / CuWO4 / Fe Foam catalyst precursor prepared in the above step was placed in a reactor for reduction. The reduction conditions were: in a 100% H2 atmosphere, the temperature was raised to 300°C at a rate of 2°C / min, and the reduction was performed for 10 hours. During the reduction process, the gas velocity was maintained at 80 mL / min to obtain a Ru / CuWO4 / Fe Foam catalyst.
[0131] The molar content ratio of Fe:Cu in the Ru / CuWO4 / Fe Foam catalyst obtained in this example is 6 from the surface to the depth of 3-10nm, wherein Fe 0 The content is 10%, Cu in Cu species 0 The content is 15%, W in W species 5+ The content is 30%, Ru in Ru species 0 The content is 0%. The above results were obtained through XPS characterization.
[0132] The Ru / CuWO4 / Fe Foam catalyst obtained above was used to carry out glucose hydrogenolysis in a continuous fixed bed reactor. The catalyst bed height was 1 cm. The reaction gas for the hydrogenolysis reaction was hydrogen, and the flow rate of hydrogen was 45 mL / (min·g cat -1 ), temperature is 245℃, pressure is 3MPa; flow rate of glucose aqueous solution is 0.2mL / (min·g cat -1 ), the concentration of glucose in the glucose aqueous solution is 50 g / L. The distribution of glucose hydrogenolysis products is shown in Table 4.
[0133] Table 4 Evaluation results of Ru / CuWO4 / Fe Foam catalyst activity for hydrogenolysis of glucose
[0134]
[0135] Others: including products such as sorbitol, hexylene glycol and n-propanol.
[0136] Example 5
[0137] A method for preparing a foam structure catalyst specifically comprises the following steps:
[0138] (1) treating nickel foam with an average pore size of 1000 μm by immersing it in 1% dilute hydrochloric acid at 45° C. for 0.5 h, washing it with water and filtering it, and then drying it in vacuum at 60° C. for 12 h;
[0139] (2) mixing an ammonium tungstate aqueous solution and a copper acetate aqueous solution in a molar ratio of 1:1 to obtain a suspension containing catalyst active sites;
[0140] (3) mixing the foamed metal material obtained in step (1) with the suspension obtained in step (2), and performing hydrothermal synthesis at 120° C. for 12 h; then performing a first drying at 100° C. for 12 h; and performing a first calcination at 600° C. for 6 h to obtain a CuWO4 / Ni Foam catalyst precursor;
[0141] (4) Rhodium chloride was dissolved in deionized water by an excess impregnation method, and Rh species was loaded on a CuWO4 / NiFoam catalyst precursor with a loading amount of 0.1 wt.%, and the catalyst was placed under negative pressure at room temperature for 10 min; then a second drying was performed at 120° C. for 10 h; and a second calcination was performed at 400° C. for 2 h to obtain a Rh / CuWO4 / Ni Foam catalyst precursor;
[0142] (5) The Rh / CuWO4 / Ni Foam catalyst precursor prepared in the above step is placed in a reactor for reduction. The reduction conditions are: in a 5% H2 atmosphere, the temperature is increased to 300°C at a rate of 2°C / min, and the reduction is performed for 10 hours. During the reduction process, the gas velocity is maintained at 120 mL / min to obtain a Rh / CuWO4 / Ni Foam catalyst.
[0143] The molar content ratio of Ni:Cu in the Rh / CuWO4 / Ni Foam catalyst obtained in this example is 7 from the surface to the depth of 3-10nm, wherein Ni 0 The content is 18%, Cu species 0 The content is 8%, W in W species 5+ The content is 40%, Rh in Rh species 0 The content is 5%. The above results were obtained through XPS characterization.
[0144] The above-obtained Rh / CuWO4 / Ni Foam catalyst was used to carry out glucose hydrogenolysis in a continuous fixed bed reactor. The catalyst bed height was 1 cm. The reaction gas for the hydrogenolysis reaction was hydrogen, and the flow rate of hydrogen was 85 mL / (min·g cat -1 ), temperature is 245℃, pressure is 4MPa; flow rate of glucose solution is 0.05mL / (min·g cat -1 ), the concentration of glucose in the glucose aqueous solution is 60 g / L. The distribution of glucose hydrogenolysis products is shown in Table 5.
[0145] Table 5 Evaluation results of the activity of Rh / CuWO4 / Ni Foam catalyst for glucose hydrogenolysis
[0146]
[0147]
[0148] Others: including products such as sorbitol, hexylene glycol and n-propanol.
[0149] Example 6
[0150] A method for preparing a foam structure catalyst specifically comprises the following steps:
[0151] (1) The foamed iron with an average pore size of 1500 μm was treated with acid by immersing it in 0.1% dilute hydrochloric acid at 25° C. for 0.5 h, washed with water and filtered, and then vacuum dried at 55° C. for 10 h;
[0152] (2) mixing a sodium tungstate aqueous solution and a cobalt chloride aqueous solution in a molar ratio of 1:1 to obtain a suspension containing catalyst active sites;
[0153] (3) mixing the foamed metal material obtained in step (1) with the suspension obtained in step (2), and performing hydrothermal synthesis at 150° C. and maintaining for 6 hours; then performing a first drying at 120° C. and maintaining for 12 hours; and performing a first calcination at 400° C. and maintaining for 3 hours, to obtain a CoWO4 / Fe Foam catalyst precursor;
[0154] (4) dissolving zinc nitrate in deionized water by an excess impregnation method, and loading the Zn species on the CoWO4 / FeFoam catalyst precursor at a loading amount of 0.5 wt.%, and standing under negative pressure for 10 min at room temperature; then performing a second drying at 120° C. for 10 h; and performing a second calcination at 400° C. for 2 h to obtain a Zn / CoWO4 / Fe Foam catalyst precursor;
[0155] (5) The Zn / CoWO4 / Fe Foam catalyst precursor prepared in the above step was placed in a reactor for reduction. The reduction conditions were: in a 100% H2 atmosphere, the temperature was raised to 300°C at a rate of 2°C / min, and the reduction was performed for 10 hours. During the reduction process, the gas velocity was maintained at 80 mL / min to obtain a Zn / CoWO4 / Fe Foam catalyst.
[0156] The molar content ratio of Fe:Co in the Zn / CoWO4 / Fe Foam catalyst obtained in this example is 8 from the surface to the depth of 3-10nm, wherein Fe 0 The content is 12%, Co in Co species 0 The content is 0%, W in W species 5+ The content is 30%, Zn in Zn species 0 The content is 0%. The above results were obtained through XPS characterization.
[0157] The Zn / CoWO4 / Fe Foam catalyst obtained above was used to carry out glucose hydrogenolysis in a continuous fixed bed reactor. The catalyst bed height was 3 cm. The reaction gas for the hydrogenolysis reaction was hydrogen, and the flow rate of hydrogen was 70 mL / (min·g cat -1), temperature is 205℃, pressure is 5MPa; flow rate of glucose aqueous solution is 0.1mL / (min·g cat -1 ), the concentration of glucose in the glucose aqueous solution is 25 g / L. The distribution of glucose hydrogenolysis products is shown in Table 6.
[0158] Table 6 Evaluation results of glucose hydrogenolysis activity of Zn / CoWO4 / Fe Foam catalyst
[0159]
[0160] Others: including products such as sorbitol, hexylene glycol and n-propanol.
[0161] Example 7
[0162] A method for preparing a foam structure catalyst specifically comprises the following steps:
[0163] (1) The foamed iron with an average pore size of 1500 μm was treated with acid by immersing it in 0.1% dilute hydrochloric acid at 25° C. for 0.5 h, washed with water and filtered, and then vacuum dried at 55° C. for 10 h;
[0164] (2) mixing a sodium tungstate aqueous solution and a cobalt acetate aqueous solution in a molar ratio of 1:1 to obtain a suspension containing catalyst active sites;
[0165] (3) mixing the foamed metal material obtained in step (1) with the suspension obtained in step (2), and performing hydrothermal synthesis at 150° C. and maintaining for 6 hours; then performing a first drying at 120° C. and maintaining for 12 hours; and performing a first calcination at 400° C. and maintaining for 3 hours, to obtain a CoWO4 / Fe Foam catalyst precursor;
[0166] (4) dissolving zirconium nitrate in deionized water by an excess impregnation method, and loading the Zr species on the CoWO4 / FeFoam catalyst precursor at a loading amount of 0.5 wt.%, and standing under negative pressure for 10 min at room temperature; then performing a second drying at 120° C. for 10 h; and performing a second calcination at 400° C. for 2 h to obtain a Zr / CoWO4 / Fe Foam catalyst precursor;
[0167] (5) The Zr / CoWO4 / Fe Foam catalyst precursor prepared in the above step was placed in a reactor for reduction. The reduction conditions were: in a 100% H2 atmosphere, the temperature was raised to 300°C at a rate of 2°C / min, and the reduction was performed for 10 hours. During the reduction process, the gas velocity was maintained at 80 mL / min to obtain a Zr / CoWO4 / Fe Foam catalyst.
[0168] The molar content ratio of Fe:Co in the Zr / CoWO4 / Fe Foam catalyst obtained in this example is 8 from the surface to the depth of 3-10nm, wherein Fe 0 The content is 12%, Co in Co species 0 The content is 0%, W in W species 5+ The content is 55%, and Zr in Zr species 0 The content is 0%. The above results were obtained through XPS characterization.
[0169] The Zr / CoWO4 / Fe Foam catalyst obtained above was used to carry out glucose hydrogenolysis in a continuous fixed bed reactor. The catalyst bed height was 3 cm. The reaction gas for the hydrogenolysis reaction was hydrogen, and the flow rate of hydrogen was 70 mL / (min·g cat -1 ), temperature is 205℃, pressure is 5MPa; flow rate of glucose solution is 0.1mL / (min·g cat -1 ), the concentration of glucose in the glucose aqueous solution is 25 g / L. The distribution of glucose hydrogenolysis products is shown in Table 7.
[0170] Table 7 Evaluation results of the activity of Zr / CoWO4 / Fe Foam catalyst for hydrogenolysis of glucose
[0171]
[0172] Others: including products such as sorbitol, hexylene glycol and n-propanol.
[0173] Figure 4 The XRD patterns of the catalysts are Fe Foam, CoWO4 / Fe Foam prepared in Example 1 and Zr / CoWO4 / Fe Foam prepared in Example 7; Figure 4 It can be seen that in the catalysts after the above-mentioned hydrogenolysis of glucose reaction, the CoWO4 species is still well preserved in the CoWO4 / FeFoam and Zr / CoWO4 / Fe Foam catalysts, indicating that the above-mentioned catalysts have good stability.
[0174] Example 8
[0175] A method for preparing a foam structure catalyst specifically comprises the following steps:
[0176] (1) The foamed iron with an average pore size of 1500 μm was treated with acid by immersing it in 0.1% dilute hydrochloric acid at 25° C. for 0.5 h, washed with water and filtered, and then vacuum dried at 55° C. for 10 h;
[0177] (2) mixing a sodium tungstate aqueous solution and a nickel acetate aqueous solution in a molar ratio of 1:1 to obtain a suspension containing catalyst active sites;
[0178] (3) mixing the foamed metal material obtained in step (1) with the suspension obtained in step (2), and performing hydrothermal synthesis at 150° C. and maintaining for 6 hours; then performing a first drying at 120° C. and maintaining for 12 hours; and performing a first calcination at 400° C. and maintaining for 3 hours, to obtain a NiWO4 / Fe Foam catalyst precursor;
[0179] (4) dissolving palladium nitrate in deionized water by an excess impregnation method, and loading the Pd species on the NiWO4 / FeFoam catalyst precursor at a loading amount of 0.5 wt.%, and standing under negative pressure for 10 min at room temperature; then performing a second drying at 120° C. for 10 h; and performing a second calcination at 400° C. for 2 h to obtain a Pd / NiWO4 / Fe Foam catalyst precursor;
[0180] (5) The Pd / NiWO4 / Fe Foam catalyst precursor prepared in the above step is placed in a reactor for reduction. The reduction conditions are: in a 100% H2 atmosphere, the temperature is increased to 300°C at a rate of 2°C / min, and the reduction is carried out for 10 hours. During the reduction process, the gas velocity is maintained at 80 mL / min to obtain a Pd / NiWO4 / Fe Foam catalyst.
[0181] The molar content ratio of Fe:Ni in the Pd / NiWO4 / Fe Foam catalyst obtained in this example is 4 from the surface to the depth of 3-10 nm, wherein Fe 0 The content is 20%, and Ni in Ni species 0 The content is 15%, W in W species 5+ The content is 32%. Pd in Pd species 0 The content is 20%, and the above results are obtained through XPS characterization.
[0182] The Pd / NiWO4 / Fe Foam catalyst obtained above was used to carry out glucose hydrogenolysis in a continuous fixed bed reactor. The catalyst bed height was 3 cm. The reaction gas for the hydrogenolysis reaction was hydrogen, and the flow rate of hydrogen was 70 mL / (min·g cat -1 ), temperature is 205℃, pressure is 5MPa; flow rate of glucose aqueous solution is 0.2mL / (min·g cat -1 ), the concentration of glucose in the glucose aqueous solution is 50 g / L. The distribution of glucose hydrogenolysis products is shown in Table 8.
[0183] Table 8 Evaluation results of glucose hydrogenolysis activity of Pd / NiWO4 / Fe Foam catalyst
[0184]
[0185] Others: including products such as sorbitol, hexylene glycol and n-propanol.
[0186] Example 9
[0187] A method for preparing a foam structure catalyst specifically comprises the following steps:
[0188] (1) The foamed iron with an average pore size of 2000 μm was treated with acid by immersing it in 0.5% dilute hydrochloric acid at 45° C. for 0.5 h, washed with water and filtered, and then vacuum dried at 60° C. for 12 h;
[0189] (2) mixing an aqueous sodium molybdate solution and an aqueous cobalt nitrate solution in a molar ratio of 1:1 to obtain a suspension containing catalyst active sites;
[0190] (3) mixing the foamed metal material obtained in step (1) with the suspension obtained in step (2), and performing hydrothermal synthesis at 120° C. for 12 hours; then performing a first drying at 100° C. for 12 hours; and performing a first calcination at 500° C. for 4 hours to obtain a CoMoO4 / Fe Foam catalyst precursor;
[0191] (4) dissolving chloroplatinic acid in deionized water by an excess impregnation method, and loading Pt species on the CoMoO4 / FeFoam catalyst precursor at a loading amount of 0.1 wt.%, and standing under negative pressure for 10 min at room temperature; then performing a second drying at 120°C for 10 h; and performing a second calcination at 400°C for 2 h to obtain a Pt / CoMoO4 / FeFoam catalyst precursor;
[0192] (5) The Pt / CoMoO4 / Fe Foam catalyst precursor prepared in the above step is placed in a reactor for reduction. The reduction conditions are: in a 100% H2 atmosphere, the temperature is increased to 300°C at a rate of 2°C / min, and the reduction is performed for 10 hours. During the reduction process, the gas velocity is maintained at 80 mL / min to obtain a Pt / CoMoO4 / Fe Foam catalyst.
[0193] The molar content ratio of Fe:Co in the Pt / CoMoO4 / Fe Foam catalyst obtained in this example is 9 from the surface to the depth of 3-10nm, where Fe 0 The content is 25%, Co in Co species 0 The content is 8%, Mo in Mo species 5+The content is 40%, and Pt in Pt species 0 The content is 33%. The above results were obtained through XPS characterization.
[0194] The Pt / CoMoO4 / Fe Foam catalyst obtained above was used to carry out glucose hydrogenolysis in a continuous fixed bed reactor. The catalyst bed height was 1 cm. The reaction gas for the hydrogenolysis reaction was hydrogen, and the flow rate of hydrogen was 35 mL / (min·g cat -1 ), temperature is 205℃, pressure is 3MPa; flow rate of glucose aqueous solution is 0.1mL / (min·g cat -1 ), the concentration of glucose in the glucose aqueous solution is 35 g / L. The distribution of glucose hydrogenolysis products is shown in Table 9.
[0195] Table 9 Evaluation results of glucose hydrogenolysis activity of Pt / CoMoO4 / Fe Foam catalyst
[0196]
[0197] Others: including products such as sorbitol, hexylene glycol and n-propanol.
[0198] Example 10
[0199] A method for preparing a foam structure catalyst specifically comprises the following steps:
[0200] (1) The foamed iron with an average pore size of 2000 μm was treated with acid by immersing it in 0.5% dilute hydrochloric acid at 45° C. for 0.5 h, washed with water and filtered, and then vacuum dried at 60° C. for 12 h;
[0201] (2) mixing an aqueous sodium tungstate solution and an aqueous zinc nitrate solution in a molar ratio of 1:1 to obtain a suspension containing catalyst active sites;
[0202] (3) mixing the foamed metal material obtained in step (1) with the suspension obtained in step (2), and performing hydrothermal synthesis at 120° C. for 12 h; then performing a first drying at 100° C. for 12 h; and performing a first calcination at 500° C. for 4 h to obtain a ZnWO4 / Fe Foam catalyst precursor;
[0203] (4) Ruthenium chloride was dissolved in deionized water by an excess impregnation method, and Pt species was loaded on the ZnWO4 / FeFoam catalyst precursor with a loading amount of 0.1 wt.%, and the mixture was placed under negative pressure at room temperature for 10 min; then a second drying was performed at 120° C. for 10 h; and a second calcination was performed at 400° C. for 2 h to obtain a Ru / ZnWO4 / Fe Foam catalyst precursor;
[0204] (5) The Ru / ZnWO4 / Fe Foam catalyst precursor prepared in the above step was placed in a reactor for reduction. The reduction conditions were: in a 100% H2 atmosphere, the temperature was raised to 300°C at a rate of 2°C / min, and the reduction was performed for 10 hours. During the reduction process, the gas velocity was maintained at 80 mL / min to obtain a Ru / ZnWO4 / Fe Foam catalyst.
[0205] The molar content ratio of Fe:Zn in the Ru / ZnWO4 / Fe Foam catalyst obtained in this example is 9 from the surface to the depth of 3-10 nm, wherein Fe 0 The content is 5%, Zn in Zn species 0 The content is 0%, W in W species 5+ The content is 30%, Ru in Ru species 0 The content is 8%. The above results were obtained through XPS characterization.
[0206] The Ru / ZnWO4 / Fe Foam catalyst obtained above was used to carry out glucose hydrogenolysis in a continuous fixed bed reactor. The catalyst bed height was 1 cm. The reaction gas for the hydrogenolysis reaction was hydrogen, and the flow rate of hydrogen was 35 mL / (min·g cat -1 ), temperature is 245℃, pressure is 3MPa; flow rate of glucose aqueous solution is 0.2mL / (min·g cat -1 ); the concentration of glucose in the glucose aqueous solution is 60 g / L. The distribution of glucose hydrogenolysis products is shown in Table 10.
[0207] Table 10 Evaluation results of Ru / ZnWO4 / Fe Foam catalyst activity for glucose hydrogenolysis
[0208]
[0209]
[0210] Others: including products such as sorbitol, hexylene glycol and n-propanol.
[0211] Embodiment 11
[0212] A method for preparing a foam structure catalyst specifically comprises the following steps:
[0213] (1) treating the nickel foam with an average pore size of 2000 μm by immersing it in 0.5% dilute hydrochloric acid at 45° C. for 0.5 h, washing it with water and filtering it, and then drying it in vacuum at 60° C. for 12 h;
[0214] (2) mixing a sodium tungstate aqueous solution and a zinc chloride aqueous solution in a molar ratio of 1:1 to obtain a suspension containing catalyst active sites;
[0215] (3) mixing the foamed metal material obtained in step (1) with the suspension obtained in step (2), and performing hydrothermal synthesis at 120° C. for 12 hours; then performing a first drying at 100° C. for 12 hours; and performing a first calcination at 500° C. for 4 hours to obtain a ZnWO4 / Ni Foam catalyst precursor;
[0216] (4) dissolving palladium nitrate in deionized water by an excess impregnation method, and loading Pt species on a ZnWO4 / NiFoam catalyst precursor at a loading amount of 0.1 wt.%, and standing under negative pressure for 10 min at room temperature; then performing a second drying at 120° C. for 10 h; and performing a second calcination at 400° C. for 2 h to obtain a Pd / ZnWO4 / Ni Foam catalyst precursor;
[0217] (5) The Pd / ZnWO4 / Ni Foam catalyst precursor prepared in the above step is placed in a reactor for reduction. The reduction conditions are: in a 100% H2 atmosphere, the temperature is increased to 300°C at a rate of 2°C / min, and the reduction is performed for 10 hours. During the reduction process, the gas velocity is maintained at 80 mL / min to obtain a Pd / ZnWO4 / Ni Foam catalyst.
[0218] The molar content ratio of Ni:Zn in the Pd / ZnWO4 / Ni Foam catalyst obtained in this example is 9 from the surface to the depth of 3-10 nm, wherein Ni 0 The content is 10%, Zn in Zn species 0 The content is 0%, W in W species 5+ The content is 30%, and Pd in Pd species 0 The content is 12%. The above results were obtained through XPS characterization.
[0219] The Pd / ZnWO4 / Ni Foam catalyst obtained above was used to carry out glucose hydrogenolysis in a continuous fixed bed reactor. The catalyst bed height was 1 cm. The reaction gas for the hydrogenolysis reaction was hydrogen, and the flow rate of hydrogen was 35 mL / (min·g cat -1 ), temperature is 245℃, pressure is 3MPa; flow rate of glucose aqueous solution is 0.2mL / (min·g cat -1 ), the concentration of glucose in the glucose aqueous solution is 40 g / L. The distribution of glucose hydrogenolysis products is shown in Table 11.
[0220] Table 11 Evaluation results of glucose hydrogenolysis activity of Pd / ZnWO4 / Ni Foam catalyst
[0221]
[0222] Others: including products such as sorbitol, hexylene glycol and n-propanol.
[0223] Example 12
[0224] A method for preparing a foam structure catalyst specifically comprises the following steps:
[0225] (1) treating the foamed cobalt with an average pore size of 2000 μm by immersing it in 0.5% dilute hydrochloric acid at 45° C. for 0.5 h, washing it with water and filtering it, and then drying it in vacuum at 60° C. for 12 h;
[0226] (2) mixing an aqueous sodium molybdate solution and an aqueous zinc acetate solution in a molar ratio of 1:1 to obtain a suspension containing catalyst active sites;
[0227] (3) mixing the foamed metal material obtained in step (1) with the suspension obtained in step (2), and performing hydrothermal synthesis at 120° C. for 12 hours; then performing a first drying at 100° C. for 12 hours; and performing a first calcination at 500° C. for 4 hours to obtain a ZnWO4 / Co Foam catalyst precursor;
[0228] (4) dissolving chloroplatinic acid in deionized water by an excess impregnation method, and loading Pt species on a ZnWO4 / CoFoam catalyst precursor at a loading amount of 0.1 wt.%, and standing under negative pressure for 10 min at room temperature; then performing a second drying at 120°C for 10 h; and performing a second calcination at 400°C for 2 h to obtain a Pt / ZnWO4 / Co Foam catalyst precursor;
[0229] (5) The Pt / ZnWO4 / Co Foam catalyst precursor prepared in the above step is placed in a reactor for reduction. The reduction conditions are: in a 100% H2 atmosphere, the temperature is increased to 300°C at a rate of 2°C / min, and the reduction is performed for 10 hours. During the reduction process, the gas velocity is maintained at 80 mL / min to obtain a Pt / ZnWO4 / Co Foam catalyst.
[0230] The molar content ratio of Co:Zn in the Pt / ZnWO4 / Co Foam catalyst obtained in this example is 7 from the surface to the depth of 3-10 nm, wherein the Co species has a Co:Zn molar content ratio of 7. 0 The content is 15%, Zn in Zn species 0 The content is 0%, W in W species 5+ The content is 30%, and Pt in Pt species0 The content is 3%. The above results were obtained through XPS characterization.
[0231] The Pt / ZnWO4 / Co Foam catalyst obtained above was used to carry out glucose hydrogenolysis in a continuous fixed bed reactor. The catalyst bed height was 1 cm. The reaction gas for the hydrogenolysis reaction was hydrogen, and the flow rate of hydrogen was 35 mL / (min·g cat -1 ), temperature is 245℃, pressure is 3MPa; flow rate of glucose aqueous solution is 0.2mL / (min·g cat -1 ), the concentration of glucose in the glucose aqueous solution is 45 g / L. The distribution of glucose hydrogenolysis products is shown in Table 12.
[0232] Table 12 Evaluation results of glucose hydrogenolysis activity of Pt / ZnWO4 / Co Foam catalyst
[0233]
[0234] Others: including products such as sorbitol, hexylene glycol and n-propanol.
[0235] Example 13
[0236] A method for preparing a foam structure catalyst specifically comprises the following steps:
[0237] (1) treating the nickel foam with an average pore size of 1500 μm by immersing it in 0.1% dilute hydrochloric acid at 25° C. for 0.5 h, washing it with water and filtering it, and then drying it in vacuum at 55° C. for 10 h;
[0238] (2) mixing a sodium tungstate aqueous solution and a nickel chloride aqueous solution in a molar ratio of 1:1 to obtain a suspension containing catalyst active sites;
[0239] (3) mixing the foamed metal material obtained in step (1) with the suspension obtained in step (2), and performing hydrothermal synthesis at 150° C. and maintaining for 6 hours; then performing a first drying at 120° C. and maintaining for 12 hours; and performing a first calcination at 400° C. and maintaining for 3 hours, to obtain a NiWO4 / Ni Foam catalyst precursor;
[0240] (4) The NiWO4 / Ni Foam catalyst precursor prepared in the above step is placed in a reactor for reduction. The reduction conditions are: in a 100% H2 atmosphere, the temperature is increased to 300°C at a rate of 2°C / min, and the reduction is carried out for 10 hours. During the reduction process, the gas velocity is maintained at 80 mL / min to obtain a NiWO4 / Ni Foam catalyst.
[0241] The surface of the NiWO4 / Ni Foam catalyst obtained in this example is within the range of 3-10nm depth: 0 The content is 25%, W in W species 5+ The content is 55%. The above results were obtained through XPS characterization.
[0242] The NiWO4 / Ni Foam catalyst obtained above was used to carry out glucose hydrogenolysis in a continuous fixed bed reactor. The catalyst bed height was 3 cm. The reaction gas for the hydrogenolysis reaction was hydrogen, and the flow rate of hydrogen was 70 mL / (min·g cat -1 ), temperature is 205℃, pressure is 5MPa; flow rate of glucose aqueous solution is 0.1mL / (min·g cat -1 ), the concentration of glucose in the glucose aqueous solution is 50 g / L. The distribution of glucose hydrogenolysis products is shown in Table 13.
[0243] Table 13 Evaluation results of the hydrogenolysis activity of NiWO4 / Ni Foam catalyst for glucose
[0244]
[0245] Others: including products such as sorbitol, hexylene glycol and n-propanol.
[0246] Embodiment 14
[0247] A method for preparing a foam structure catalyst specifically comprises the following steps:
[0248] (1) The foamed iron with an average pore size of 1500 μm was treated with acid by immersing it in 0.1% dilute hydrochloric acid at 25° C. for 0.5 h, washed with water and filtered, and then vacuum dried at 55° C. for 10 h;
[0249] (2) mixing an aqueous sodium tungstate solution and an aqueous ferrous nitrate solution in a molar ratio of 1:1 to obtain a suspension containing catalyst active sites;
[0250] (3) mixing the foamed metal material obtained in step (1) with the suspension obtained in step (2), and performing hydrothermal synthesis at 150° C. and maintaining for 6 hours; then performing a first drying at 120° C. and maintaining for 12 hours; and performing a first calcination at 400° C. and maintaining for 3 hours, to obtain a FeWO4 / Fe Foam catalyst precursor;
[0251] (4) The FeWO4 / Fe Foam catalyst precursor prepared in the above step was placed in a reactor for reduction. The reduction conditions were: in a 100% H2 atmosphere, the temperature was raised to 300°C at a rate of 2°C / min, and the reduction was performed for 10 hours. During the reduction process, the gas velocity was maintained at 50 mL / min to obtain a FeWO4 / Fe Foam catalyst.
[0252] The surface of the FeWO4 / Fe Foam catalyst obtained in this example is within the range of 3-10nm depth: 0 The content is 20%, W in W species 5+ The content is 35%. The above results were obtained through XPS characterization.
[0253] The FeWO4 / Fe Foam catalyst obtained above was used to carry out glucose hydrogenolysis in a continuous fixed bed reactor. The catalyst bed height was 3 cm. The reaction gas for the hydrogenolysis reaction was hydrogen, and the flow rate of hydrogen was 70 mL / (min·g cat -1 ), temperature is 205℃, pressure is 5MPa; flow rate of glucose aqueous solution is 0.1mL / (min·g cat -1 ), the concentration of glucose in the glucose aqueous solution is 55 g / L. The distribution of glucose hydrogenolysis products is shown in Table 14.
[0254] Table 14 Evaluation results of the activity of FeWO4 / Fe Foam catalyst for hydrogenolysis of glucose
[0255]
[0256]
[0257] Others: including products such as sorbitol, hexylene glycol and n-propanol.
[0258] Embodiment 15
[0259] The CoWO4 / Fe Foam catalyst was prepared according to the method of Example 1, except that the glucose hydrogenolysis reaction temperature was 245° C. The distribution of glucose hydrogenolysis reaction products is shown in Table 15.
[0260] Table 15 Evaluation results of the activity of CoWO4 / Fe Foam catalyst for hydrogenolysis of glucose
[0261]
[0262] a: Other products include sorbitol, hexylene glycol and n-propanol.
[0263] Example 16
[0264] The Zr / CoWO4 / Fe Foam catalyst was prepared according to the method of Example 7, except that zirconium nitrate was replaced by zirconium oxynitrate as the precursor for loading. The distribution of glucose hydrogenolysis reaction products is shown in Table 16.
[0265] Table 16 Evaluation results of glucose hydrogenolysis activity of Zr / CoWO4 / Fe Foam catalyst
[0266]
[0267] Others: including products such as sorbitol, hexylene glycol and n-propanol.
[0268] Comparative Example 1
[0269] The CoWO4 catalyst was prepared according to the method of Example 13, except that step (1) was not included. The preparation method of the CoWO4 catalyst specifically comprises the following steps:
[0270] (1) mixing a sodium tungstate aqueous solution and a cobalt chloride aqueous solution in a molar ratio of 1:1 to obtain a suspension containing catalyst active sites; performing hydrothermal synthesis at 150° C. and maintaining for 6 hours; then performing a first drying at 120° C. and maintaining for 12 hours; and performing a first calcination at 400° C. and maintaining for 3 hours to obtain a CoWO4 catalyst precursor;
[0271] (2) The catalyst precursor prepared in the above step is placed in a reactor for reduction. The reduction conditions are: in a 100% H2 atmosphere, the temperature is raised to 300°C at a rate of 2°C / min, and the reduction is performed for 10 hours. During the reduction process, the gas velocity is maintained at 80 mL / min to obtain a CoWO4 catalyst.
[0272] The surface of the CoWO4 catalyst obtained in this example is within the range of 3-10nm depth: Co 0 The content is 0%, W in W species 5+ The content is 40%. The above results were obtained through XPS characterization.
[0273] The CoWO4 catalyst obtained above was used to carry out glucose hydrogenolysis in a continuous fixed bed reactor. The catalyst bed height was 3 cm. The reaction gas for the hydrogenolysis reaction was hydrogen, and the flow rate of hydrogen was 70 mL / (min·g cat -1 ), temperature is 205℃, pressure is 5MPa; flow rate of glucose aqueous solution is 0.1mL / (min·g cat -1 ), the concentration of glucose in the glucose aqueous solution is 25 g / L. The distribution of glucose hydrogenolysis products is shown in Table 17.
[0274] Table 17 Evaluation results of the activity of CoWO4 catalyst for hydrogenolysis of glucose
[0275]
[0276] Others: including products such as sorbitol, hexylene glycol and n-propanol.
[0277] By comparing Comparative Example 1 with Example 1, it is found that the glucose conversion rate of Comparative Example 1 is 19.0%, and the selectivity of 1,3-propylene glycol is 4.8%; while the glucose conversion rate in Example 1 can reach 100%, and the selectivity of 1,3-propylene glycol can reach 55.9%; the reason for this may be that the zero-valent metal generated after the foam metal in the foam structure catalyst of Example 1 is reduced promotes the hydrogenation reaction during the reaction, thereby promoting the hydrogenolysis of glucose into 1,3-propylene glycol.
[0278] Comparative Example 2
[0279] The CoWO4 catalyst was prepared according to the method of Example 13, except that step (2) was not included. The preparation method of the foam structure catalyst specifically comprises the following steps:
[0280] (1) The foamed iron with an average pore size of 1500 μm was treated with acid by immersing it in 0.1% dilute hydrochloric acid at 25° C. for 0.5 h, washed with water and filtered, and then vacuum dried at 55° C. for 10 h;
[0281] (2) subjecting the foamed metal material obtained in step (1) to hydrothermal synthesis at 150° C. and maintaining for 6 h; then subjecting the foamed metal material to a first drying step at 120° C. and maintaining for 12 h; and subjecting the foamed metal material to a first calcination step at 400° C. and maintaining for 3 h; and obtaining a FeFoam catalyst precursor;
[0282] (3) The catalyst precursor prepared in the above step is placed in a reactor for reduction. The reduction conditions are: in a 100% H2 atmosphere, the temperature is increased to 300°C at a rate of 2°C / min, and the reduction is carried out for 10 hours. During the reduction process, the gas velocity is maintained at 80 mL / min to obtain a Fe Foam catalyst.
[0283] The Fe Foam catalyst obtained in this example has a surface area of 3-10 nm and a depth of 10 nm. 0 The content is 25%.
[0284] The Fe Foam catalyst obtained above was used to carry out glucose hydrogenolysis in a continuous fixed bed reactor. The catalyst bed height was 3 cm. The reaction gas for the hydrogenolysis reaction was hydrogen, and the flow rate of hydrogen was 70 mL / (min·g cat -1), temperature is 205℃, pressure is 5MPa; flow rate of glucose aqueous solution is 0.1mL / (min·g cat -1 ), the concentration of glucose in the glucose aqueous solution is 25 g / L. The distribution of glucose hydrogenolysis products is shown in Table 18.
[0285] Table 18 Evaluation results of Fe Foam catalyst hydrogenolysis glucose activity
[0286]
[0287] Others: including products such as sorbitol, hexylene glycol and n-propanol.
[0288] By comparing Comparative Example 2 with Example 1, it is found that the glucose conversion rate of Comparative Example 2 is 21.2%, and the selectivity of 1,3-propylene glycol is 2.2%; while the glucose conversion rate in Example 1 can reach 100%, and the selectivity of 1,3-propylene glycol can reach 55.9%; although the Fe Foam catalyst has a higher content of Fe 0 The absence of the CoWO4 acidic site in the catalyst reduces the B acidic site in the catalyst, thereby inhibiting the formation of 1,3-propylene glycol in the glucose conversion. Therefore, in Example 1, the synergistic effect between the hydrogenation active site and the acidic active site constructed in the CoWO4 / Fe Foam catalyst is the key active site for realizing the hydrogenolysis conversion of glucose into 1,3-propylene glycol.
[0289] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A foam structure catalyst, characterized in that: The foam structure catalyst comprises a foam structure and a metal M2, a metal oxide M2O grown on the foam structure x and a heteropolyacid salt of a metal M2 and optionally tungsten oxide WO z1 and optionally molybdenum oxide MoO z2, , z1=2-3, z2=2-3; wherein the heteropoly acid salt is selected from one or more of tungstate and molybdate, M2 is selected from one or more of Cu, Ni, Fe, Zn and Co, x=0.5-1.5; the foam structure contains metals M1 and M1O y , M1 is selected from one or more of foamed iron, foamed nickel and foamed cobalt, and y=1-1.
5.
2. The foam structure catalyst according to claim 1, wherein In the range from the surface of the foam structure catalyst to a depth of 3-10 nm: the molar ratio of M1:M2 is 4-9; wherein, M1 in the M1 species 0 The content of M2 is 5-25%, and M2 in M2 species 0 The content of tungsten species is 0-15%. 5+ The content is 30-55%, Mo in molybdenum species 5+ The content is 25-45%.
3. The foam structure catalyst according to claim 1 or 2, wherein: The foam structure catalyst further comprises a metal M3 and an optional M3O supported on the foam structure and the heteropolyacid salt. z , wherein M3 is selected from one or more of Ru, Rh, Pd, Pt, Zr and Zn, 0 <z≤0-2; Preferably, within the range of 3-10 nm from the surface of the foam structure catalyst: M3 and M3O z The total molar content is: 0-5%, among which M3 0 The content is 0-50%.
4. The foam structure catalyst according to any one of claims 1 to 3, wherein: The average pore size of the foam structure catalyst is 400-3000 μm; And / or, the surface of the foam structure catalyst has metal hydrogenation active sites and acid active sites.
5. A method for preparing a foam structure catalyst, characterized in that: The preparation method comprises: (1) pre-treating the foam structure material to obtain a foam structure precursor; (2) mixing a solution of a soluble tungsten salt and a solution of a metal M2 salt, or mixing a solution of a soluble molybdenum salt and a solution of a metal M2 salt to obtain a suspension of a heteropolyacid salt; (3) mixing the foam structure precursor obtained in step (1) with the suspension of heteropolyacid salt obtained in step (2), and then performing hydrothermal synthesis, and then performing a first drying and a first calcination to obtain a first catalyst precursor; (4) The first catalyst precursor obtained in step (3) is subjected to reduction treatment to obtain a foam structure catalyst.
6. The preparation method according to claim 5, wherein: The foam structural material is selected from one or more of foamed iron, foamed nickel and foamed cobalt; preferably, the average pore size of the foam structural material is 400-3000 μm; And / or, the soluble tungsten salt is selected from one or more of sodium tungstate, ammonium metatungstate and ammonium tungstate; And / or, the soluble molybdenum salt is selected from sodium molybdate and / or ammonium molybdate; And / or, the metal M2 salt is selected from one or more of cupric chloride, cupric nitrate, cupric acetate, nickel chloride, nickel nitrate, nickel acetate, ferrous chloride, ferrous nitrate, zinc chloride, zinc nitrate, zinc acetate, cobalt chloride, cobalt nitrate and cobalt acetate; preferably cupric chloride and / or cobalt chloride; And / or, the molar ratio of the sum of the soluble tungsten salt and the soluble molybdenum salt to the metal M2 salt is 0.5-1.5:
1.
7. The preparation method according to claim 5 or 6, wherein: The pretreatment comprises: treating with dilute acid at a temperature of 20-35°C for 0.5-1h, washing with water and filtering, and vacuum drying at 55-65°C for 10-14h; preferably, the dilute acid is selected from dilute hydrochloric acid or dilute nitric acid; further preferably, the molar concentration of the dilute acid is 0.1-1%; And / or, the conditions of the hydrothermal synthesis include: temperature of 110-150° C., time of 6-24 h; And / or, the first drying temperature is 60-120°C and the time is 10-12h; And / or, the first calcination temperature is 400-600°C and the time is 3-8h; And / or, the conditions of the reduction treatment include: in a reducing gas with a H2 volume concentration of 5%-100%, heating to 200-500°C at a rate of 1-10°C / min, and keeping warm for 1-20h; preferably, the gas velocity of the reducing gas is 20-120mL / min.
8. The preparation method according to any one of claims 5 to 7, wherein: Between step (3) and step (4), the method further includes: (3') impregnating the first catalyst precursor obtained in step (3) with a solution of a metal M3 salt by an excess impregnation method, placing the catalyst precursor under negative pressure, and then performing a second drying and a second calcination to obtain a second catalyst precursor; (4) The second catalyst precursor obtained in step (3') is subjected to reduction treatment to obtain a foam structure catalyst.
9. The preparation method according to claim 8, wherein: The metal M3 salt is selected from one or more of ruthenium nitrate, ruthenium chloride, rhodium nitrate, palladium nitrate, diamine dinitrate diammine platinum, chloroplatinic acid, zirconium oxynitrate, zirconium nitrate and zinc nitrate; more preferably selected from one or more of ruthenium nitrate, rhodium nitrate, palladium nitrate, diamine dinitrate diammine platinum and zirconium nitrate; And / or, the negative pressure static conditions include: temperature of 20-30°C, pressure of -0.05 to -0.07 MPa, and time of 5-10 min; And / or, the second drying temperature is 80-120°C and the time is 10-12h; And / or, the second calcination temperature is 400-600°C and the time is 2-6h; And / or, the loading amount of the M3 salt calculated as M3 is 0.1-0.5 wt %.
10. A foam structure catalyst obtained by the preparation method according to any one of claims 5 to 9.
11. Use of the foam structure catalyst according to any one of claims 1 to 4 or the foam structure catalyst according to claim 10 in stabilizing the hydrogenolysis of glucose.
12. A method for stabilizing hydrogenolysis of glucose, characterized in that: The method comprises: In the presence of the foam structure catalyst according to any one of claims 1 to 4 or the foam structure catalyst according to claim 10, a glucose aqueous solution is subjected to hydrogenolysis reaction to obtain a C1-C4 monohydric alcohol and / or a C2-C4 dihydric alcohol.
13. The method according to claim 12, wherein: The hydrogenolysis reaction temperature is 175-295°C and the pressure is 3-5MPa; And / or, the reaction gas of the hydrogenolysis reaction is hydrogen, and the flow rate of hydrogen is 35-95 mL / (min·g cat -1 ); And / or, the concentration of glucose in the glucose aqueous solution is 25-80 g / L, and the flow rate of the glucose aqueous solution is 0.05-2 mL / (min·g cat -1 ); And / or, the hydrogenolysis reaction is carried out in a continuous fixed bed reactor, and the height of the catalyst bed is 0.5-3 cm.
14. The preparation method according to claim 12 or 13, wherein: The molar selectivity of 1,3-propylene glycol is 5-55%, and the molar selectivity of ethanol is 10-48%.
Citation Information
Cited By
Zn-Pd bimetal hierarchical pore ZSM-5 molecular sieve and preparation method and application thereof
CN120861136A